Comparison of some exogeneous solubillizing phosphate bacteria on Andisol as Indonesia dominant native tea soil - Setiawati, Mieke Rochimi; Pranoto, Eko (Jurnal Penelitian Teh dan Kina, 2015)
Tea was planting an upland area with Andisol as the dominant soil ordo. Andisol has a special characteristic i.e. low soil pH and it has more mineral that causing low of soil phos-phate soluble, especially for tea plants, there-fore the rule of solubilizing phosphate bacteria will be needed. Laboratory scale experiments were conducted to study the capability activities of some solubilizing phosphate bacterias name-ly Pseudomonas cepaceae, P. malei, Bacillus mycoides, and B. subtilis. The experiment was arranged in Completely Randomized Design with six treatments and four replications. The result on statistical analysis shown that there were no significant differences in increasing of the soil phosphate soluble. Nevertheless, the treatment D (Bacillus mycoides) produced the highest soil phosphate soluble. The capability of bacteria to increase soil phosphate soluble was depended on its habitat, especially soil pH. Even all of the isolates were the superior solubilizing phosphate bacterias in agricultural food plants with neutral soil pH, but they have not significantly different on Andisol. There-fore, the using of indigenous isolates on tea plant areas was suggested.